Bicycle Mower With Rake / Nor Shuhadah Mohamad Saian - Mohamad Saian, Nor Shuhadah (2020)
Nowadays, people anticipating for new innovation or invention to help them in their daily routine. Our Bicycle Mower with Rake will help the owner saving energy and time. The main reason that makes this lamp so original is that the combination between mower and rake. Namely, this product help the owner to save time for raking after mowing because it can do both mowing and raking in the same time. MSN Trading Sdn. Bhd. provide variety size and colour according to customer demands. The company will introduce this new technology to public, in order to find help the customer save time in landscaping their lawn. The components of the product is adult bicycle, rotary mower, leaf rake and a petrol powered motor. Customers can buy the product through retailer or go to the company official website to purchase it. Other than that, the customer can customized the product by choosing, size and colour of bicycle, size of rotary mower and size and type of leaf rake at the official website. The major purchasers are the schools, universities, municipal council and companies that provide lawn services. Since this product is from local company, the product pricing is much cheaper compared to companies from outside of Malaysia but with the same quality. In addition to that, our company is the first one to commercialized a combination between bicycle, lawn mower and rake. Therefore, our company have more advantage compared to other local product.